An opportunistic qualitative evaluation of the acceptability and feasibility of remote cognitive behavioral group intervention for bipolar disorder - Newton, Elizabeth; Copello, Alex; Rolfe, Alison; Edwards, Katie; Moonakova, Sarah; Kaufman, Arielle; Yagnik, Radha; James, Olivia; Leadbitter, Anne; Matharu, Gurvir (Frontiers in Psychology, 2025)
IntroductionIn response to the COVID-19 pandemic, many mental health services had to adapt the way in which their services were delivered. Research exploring the effectiveness of remote therapy and interventions, especially within the bipolar disorder population, is lacking. The pandemic presented an opportunity to conduct an opportunistic evaluation of a group CBT intervention for bipolar disorder which began face-to-face and transitioned to remote delivery. Service users had a unique experience of having experienced both delivery methods during the same intervention. The intervention had not previously been adapted or investigated in terms of online delivery and it was imperative to gain in-depth insight into service users and staff member’s experiences. The overarching aim of this evaluation was to provide qualitative insight into service users’ and staff members’ experiences of the feasibility and acceptability of online as compared and contrasted to face-to-face CBT intervention for bipolar disorder.MethodsA qualitative method was used to provide an in-depth, contextualized understanding of individual perceptions and experiences of two contrasting group delivery formats, face-to-face and remote. Individual interviews were undertaken with service users and a focus group was held with staff facilitating the group. Data were analyzed using thematic analysis.ResultsThe evaluation suggests that using video technology can be an effective way of delivering intervention to this client group and may have additional benefits such as easier access for some service users by reducing need to travel, easier access when struggling with mental health and aid in concentration when processing the group content. Collectively the analyses suggest that before embracing the use of technology for delivering psychological group interventions, we need to be cautious and consider clinical, group and practical processes that may be impacted and work towards diminishing these drawbacks. These factors and processes are discussed, including symptom management, accessibility, relationships and bonding, risk management and introducing a hybrid model.DiscussionThis study provides initial support for the feasibility of delivering group CBT for bipolar disorder online and its acceptability. However, it also highlights some challenges and clinical considerations. Moving forward, services could consider offering service users a choice of either face-to-face or online delivery which may widen access to psychological interventions and promote inclusivity. Further research, both qualitative and quantitative, is needed within the bipolar population to explore remote delivery and help guide services when delivering online psychological interventions.